Mapping users’ participation in brand publics: Toward a typology of styles of digital consumption - Caliandro, Alessandro; Anselmi, Guido; Arvidsson, Adam (Mediascapes journal, 2024)
This is a methodological contribution aimed at providing researchers with some practical guidance to better and more thoroughly map brand publics. The notion of brand public is steadily gaining traction in digital media and consumer culture research, especially so in studies that address liquid and platformized forms of consumption characteristic of social media. However, despite the growing academic interest in this concept, there is still a lack of methodological research in this area. In particular, one of the major methodological gaps consists in the fact that studies on brand publics fail in proposing a typology of the different kinds of users participating in them. In order to fill this gap, we propose an ad hoc typology of users participating in a brand public based on the different digital practices through which they use the digital devices that structure the public itself – rather than on users’ individual status. To this purpose we identify three main types of styles of participation in brand publics: brand loving, visibility seeking, everyday storytelling. To do that we draw on a dataset of 488,365 Instagram posts marked with the hashtag #starbucks, that we explored using digital methods. The article contribution is twofold: it provides the reader with systematic methodological guidelines and it expands the theoretical boundaries of the brand public’s notion.